The NF-κB signaling network in the life of T cells - Daniels, Mark A.; Teixeiro, Emma (Frontiers in Immunology, 2025)
NF-κB is a crucial transcription factor in lymphocyte signaling. It is activated by environmental cues that drive lymphocyte differentiation to combat infections and cancer. As a key player in inflammation, NF-κB also significantly impacts autoimmunity and transplant rejection, making it an important therapeutic target. While the signaling molecules regulating this pathway are well-studied, the effect of changes in NF-κB signaling levels on T lymphocyte differentiation, fate, and function is not fully understood. Advances in computational biology and new NF-κB-inducible animal models are beginning to clarify these questions. In this review, we highlight recent findings related to T cells, focusing on how environmental cues affecting NF-κB signaling levels determine T cell fate and function.